Tanycarpa broadi sp. nov., a new Neotropical species of the genus Tanycarpa Foerster, 1863 (Hymenoptera: Braconidae: Alysiinae), with a key to the New World taxa - Peris-Felipo, Francisco Javier; Belokobylskij, Sergey A. (Zootaxa, 2019)
A new species of alysiine wasp from Brazil, Tanycarpa broadi sp. nov., is described and illustrated. A key for determination of all known Neotropical species of Tanycarpa is provided.